2019
DOI: 10.3390/v11090859
|View full text |Cite
|
Sign up to set email alerts
|

Recombination in Enteroviruses, a Multi-Step Modular Evolutionary Process

Abstract: RNA recombination is a major driving force in the evolution and genetic architecture shaping of enteroviruses. In particular, intertypic recombination is implicated in the emergence of most pathogenic circulating vaccine-derived polioviruses, which have caused numerous outbreaks of paralytic poliomyelitis worldwide. Recent experimental studies that relied on recombination cellular systems mimicking natural genetic exchanges between enteroviruses provided new insights into the molecular mechanisms of enteroviru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
68
0
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(87 citation statements)
references
References 203 publications
(434 reference statements)
5
68
0
10
Order By: Relevance
“…Our analyses showed that recombination can readily occur in FMDV, especially among Euro-Asiatic serotypes and among SAT serotypes, www.nature.com/scientificreports/ but the process is likely largely constrained by epistatic interaction between regions coding for functionally related proteins, resulting in relatively clear mosaic genomic blocks of low recombination-rate regions as previously noted [17][18][19] . This phenomenon has in fact also been observed in other viruses 31,32 . Given how common it is, recombination likely plays an important role in survival and adaption of viruses in the face of new environments.…”
Section: Conclusion and Final Remarkssupporting
confidence: 77%
“…Our analyses showed that recombination can readily occur in FMDV, especially among Euro-Asiatic serotypes and among SAT serotypes, www.nature.com/scientificreports/ but the process is likely largely constrained by epistatic interaction between regions coding for functionally related proteins, resulting in relatively clear mosaic genomic blocks of low recombination-rate regions as previously noted [17][18][19] . This phenomenon has in fact also been observed in other viruses 31,32 . Given how common it is, recombination likely plays an important role in survival and adaption of viruses in the face of new environments.…”
Section: Conclusion and Final Remarkssupporting
confidence: 77%
“…It can involve replicative or non-replicative mechanisms [ 2 , 3 ] and potentially serves functions that include the purging of deleterious mutations and the creation of advantageous novel genetic combinations to evade host immunity, gain resistance to antiviral agents, alter virulence and expand the host range [ 1 , 4 , 5 ]. Molecular epidemiological studies, for example, of circulating enteroviruses, have shown that recombination is a frequent occurrence in picornaviruses (e.g., [ 6 , 7 , 8 ]), and analysis of viral metagenomic data has emphasized the importance of recombination in the acquisition of novel sequences and, consequently, in the evolution of viruses [ 9 , 10 ]. In contrast to nucleotide substitution, which only allows gradual searching through evolutionary fitness space, recombination can lead to large shifts that can create beneficial genetic diversity but may also disrupt favorable combinations of co-adapted alleles [ 1 , 11 ].…”
Section: Recombination As a Motive Force In Viral Evolutionmentioning
confidence: 99%
“…Improvements in viral genomic sequencing methods have facilitated the detection of recombinants, leading to accelerated detection of these events over the past decade. Enteroviruses have been frequently observed to recombine to permit the emergence of new viral strains [127,128], and indeed OPV and circulating enteroviruses also have the capacity to generate recombinants with enhanced pathogenicity and fitness [129]. Recombination events are also frequent in human and animal AstV [130] and NoV [131].…”
Section: Viral Recombination or Reassortmentmentioning
confidence: 99%